2011
DOI: 10.1080/10615806.2010.482985
|View full text |Cite
|
Sign up to set email alerts
|

Relations between a ruminative thinking style and obsessive–compulsive symptoms in non-clinical samples

Abstract: There is tremendous interest in understanding the cognitive processes behind obsessive-compulsive disorder (OCD). Whereas previous research on cognitive OCD models has focused on the dysfunctional content of obsessional thinking, processes and styles of thinking have not yet been investigated. The present study investigated the relationship between a ruminative response style and obsessive-compulsive (OC) symptomatology in two non-clinical samples. In Sample 1, 261 students completed the Ruminative Response Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 20 publications
4
30
0
Order By: Relevance
“…Although depressive rumination may result in a sense of increased insight into one's problems, feelings, and symptoms (Lyubomirsky & Nolen-Hoeksema, 1993;Papageorgiou & Wells, 2001;Watkins & Moulds, 2005), depressive rumination has also been found to exacerbate existing levels of negative mood (Lavender & Watkins, 2004;Watkins & Teasdale, 2001), increase negative thinking (Lyubomirsky & Nolen-Hoeksema, 1995), and impair concentration and central executive functioning (Lyubomirsky, Kasri, & Zehm, 2003;Watkins & Brown, 2002). The presence of depressive rumination has been well established in depression (Riso et al, 2003), but also in a range of other axis I disorders, including bipolar disorder (Gruber, Eidelman, Johnson, Smith, & Harvey, 2011), alcohol use disorders (Caselli, Bortolai, Leoni, Rovetto, & Spada, 2008), obsessive-compulsive disorder (Wahl, Ertle, Bohne, Zurowski, & Kordon, 2011), post-traumatic stress disorder (Ehring, Frank, & Ehlers, 2008), and schizophrenia (Badcock, Paulik, & Maybery, 2011).…”
Section: Practitioner Pointsmentioning
confidence: 99%
“…Although depressive rumination may result in a sense of increased insight into one's problems, feelings, and symptoms (Lyubomirsky & Nolen-Hoeksema, 1993;Papageorgiou & Wells, 2001;Watkins & Moulds, 2005), depressive rumination has also been found to exacerbate existing levels of negative mood (Lavender & Watkins, 2004;Watkins & Teasdale, 2001), increase negative thinking (Lyubomirsky & Nolen-Hoeksema, 1995), and impair concentration and central executive functioning (Lyubomirsky, Kasri, & Zehm, 2003;Watkins & Brown, 2002). The presence of depressive rumination has been well established in depression (Riso et al, 2003), but also in a range of other axis I disorders, including bipolar disorder (Gruber, Eidelman, Johnson, Smith, & Harvey, 2011), alcohol use disorders (Caselli, Bortolai, Leoni, Rovetto, & Spada, 2008), obsessive-compulsive disorder (Wahl, Ertle, Bohne, Zurowski, & Kordon, 2011), post-traumatic stress disorder (Ehring, Frank, & Ehlers, 2008), and schizophrenia (Badcock, Paulik, & Maybery, 2011).…”
Section: Practitioner Pointsmentioning
confidence: 99%
“…Across these disorders, there are topographical differences in RNT content (e.g., worry about the future in GAD, rumination about the past in MDD, compulsive repetitive thoughts in OCD) but a core construct also seems to be shared (Ehring et al 2011;McEvoy et al 2010). Disorder specific forms of RNT (e.g., worry and rumination) are associated with greater distress (Demeyer et al 2012;McEvoy and Brans 2013;Starr and Davila 2012), future depressive symptoms (Abela et al 2002;Nolen-Hoeksema 1991), and increased anxious symptoms (Blagden and Craske 1996;Calmes and Roberts 2007;Hong 2007;McEvoy and Brans 2013;Wahl et al 2011) in clinical and non-clinical samples. Further, inducing RNT in non-clinical samples has been shown to prolong negative affect and negatively impact cognitive, behavioral, and interpersonal performance (for review see Watkins 2008).…”
Section: Introductionmentioning
confidence: 95%
“…Rumination, thoughts about past events, as well as anxiety about possible danger in future, has been suggested to be both a symptom of posttraumatic stress disorder (PTSD), and also an important maintaining factor of PTSD (Ehlers & Clark, 2000). Studies have shown that there is a positive correlation between severity of obsessive compulsive symptoms and obsessive rumination, even after controlling for depression (Wahl, Ertle, Bohne, Zurowski, & Kordon, 2011). Similarly, people who score high on covert narcissism tend to have high levels of expected rumination (Atlas & Them, 2008).…”
Section: Behavioral Problemsmentioning
confidence: 99%